Critical overview on the green synthesis of carbon quantum dots and their application for cancer therapy. Issue 4 (1st April 2021) - Desmond, Liam Joseph; Phan, Anh N.; Gentile, Piergiorgio
Abstract : A critical review which delves into the advantages of the use of carbon quantum dots (CQDs) in nano-based cancer therapy, which includes its more positive environmental impact compared to previous systems. Abstract : Cancer therapeutic systems can help to confront and overcome many different strands of tumours in clinical patients. Despite the benefits, current therapeutic systems present clear unmet challenges, such as their toxicity and damaging effects to human body cells and the host. The need for easy-to-fabricate, safe and non-toxic therapeutic systems has driven the research field towards the use of carbon quantum dots. Their bioimaging with green, non-toxic, biocompatible and attractive quantum properties present them as distinctively advantageous over conventional/metal-based quantum dots. In this review, the current progress in the development of quantum dots, focusing on carbon quantum dots for use in nanotheranostics for different tumours, will be critically analysed. The advantages of applying carbon quantum dots by green bottom-up approaches into nanotherapy systems will be highlighted. Finally, ongoing challenges and opportunities associated with a green and sustainable synthesis of carbon quantum dots with specific functional groups to aid the next stages in the development of the nanotherapy system will also be discussed.